Composites of Reduced Graphene Oxide/Nickel Submicrorods for Non-Enzymatic Electrochemical Biosensing: Application to Amperometric Glucose Detection. Issue 8 (20th May 2020) - Mohammadzadeh, Amirmahdi; Mazaheri, Mozhdeh; Sedighian, Armin; Ghanbari, Hajar; Simchi, Abdolreza
Abstract : For the rapid detection of hyperglycemia in human blood, we adopted a facile and two-step electrochemical procedure to prepare nickel/reduced graphene oxide (rGO) hybrid electrodes in the framework of a three-dimensional (3D) nanostructure. High-density and vertically-aligned nickel submicrorods with an average diameter of 155 ± 15 nm and a length of 7 ± 1 μ m (an aspect ratio of about 40–50) were prepared by template-mediated electrochemical deposition techniques. Networks of rGO nanosheets between the rod-shaped arrays were formed by the cathodic electrophoretic deposition method. The synergistic effect of nickel morphology (planar and high-density rod-shaped arrays) and graphene oxide nanosheets on the electrochemical glucose oxidation in both simulated and real samples (human blood serum) were studied. It is shown that the higher surface area of Ni submicrorods significantly enhances the sensitivity of glucose detection by 6-fold (659.5 μ A mM −1 cm −2 ) as compared with planar Ni (113 μ A mM −1 cm −2 ) while the limit of detection (LOD at S/N = 3) is reduced by ∼62% (from 0.13 mM to 0.05 mM). In the presence of reduced graphene oxide nanosheets, enhanced surface contacts between the metal submicrorods and the carbon nanostructure facilitate electron transfer through surface OH − motifs, further improving the sensitivity to 7121 μ A mM −1 cm −2 . A better LOD (0.5 μ M) is also attained. The application of the electrode for glucose detection in human blood serum, i.e., fast detection (<3 s) with relatively high precision (94% confidence), is demonstrated.